Tradicals, Pillars and Directions For Educational Curriculum Development In Indonesia: A Literature Study - Ghani, Abdul; Triono, Mukhlas (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
This paper aims to identify curriculum traditions, including curriculum changes from time to time in the history of Indonesian education, the five pillars of curriculum development as considerations in curriculum development, and to see the direction of curriculum development. The author used 17 references from scientific journals and books in this study. Tracking reference sources using Google Scholar. The study results show that the educational curriculum change is greatly influenced by political factors such as the change of government and the minister in charge of education, as well as by the shift in education policy. There are five pillars of curriculum development: curriculum objectives, content or materials, learning strategies, curriculum organization and evaluation. The current curriculum development direction focuses on technology integration through the Independent Curriculum platform. As for universities, they implement Independent Learning Independent Campus, which is expected to answer global challenges and prepare the generation to face an increasingly complex world.